Fusing Carborane Carboxylic Acids with Alkynes: 3D Analogues of Isocoumarins via Regioselective B−H Activation. Issue 3 (25th October 2017) - Lin, Furong; Shen, Yunjun; Zhang, Yuanbin; Sun, Yuji; Liu, Jiyong; Duttwyler, Simon
Abstract: An iridium‐catalyzed alkenylation/annulation sequence between monocarba‐ closo ‐dodecaborate carboxylic acids and diarylacetylenes is reported. Regioselective activation of the B2 position, followed by B−C bond formation and ring closure, affords 3D bora‐analogues of isocoumarins. The reaction tolerates a variety of functional groups on the aromatic rings and can be extended to B12‐substituted derivatives. Furthermore, subsequent alkenylation of the B4 vertex has been achieved in high yields. Abstract : Get 3D ! An iridium‐catalyzed alkenylation/annulation sequence between carborane carboxylic acids and alkynes is reported. Regioselective activation of the B2 position, followed by B−C bond formation and ring closure, affords 3D bora‐analogues of isocoumarins.